Marine Impacts of Seawater Desalination : Science, Management, and Policy - Kress, Nurit (Elsevier, 2019)
Seawater desalination is increasing globally, and in light of this, it is necessary to look at the environmental and ecological impacts of desalination plants on the marine environment. Marine Impacts of Seawater Desalination: Science, Management, and Policy combines existing studies and new research into a unified work describing the interplay of seawater desalination and the marine environment. In particular, the book identifies knowledge gaps in the current data and recommends future research paths. The book also covers the established and emerging desalination processes and the policies and regulations applied to seawater desalination. Marine Impacts of Seawater Desalination is an ideal reference for engineers and developers working on environmental-related issues of seawater desalination, scientists and researchers studying these issues, as well as regulators and decision makers who can use this book as a useful guide for planning and operating desalination plants.